Hypoxia and temperature: does hypoxia affect caiman embryo differentiation rate or rate of growth only? - Iungman, Josefina Luciana (2013)
In crocodilians, the rate of embryonic development and consequently many posthatch attributes are affected by temperature. Since temperature exhibits strong influences on fitness (embryo survivorship and phenotype) by shaping development, we manipulated oxygen concentration in order to uncouple the effects of developmental rate from the direct effects of temperature. Here we consider whether oxygen constrains either differentiation rate (progression from one stage to the next) or embryonic growth (size). Thus, we incubated Caiman latirostris eggs at various oxygen concentrations, and at two temperatures (31 °C, 100% female-producing temperature, and 33 °C, 100% male-producing temperature). We monitored the developmental stages of these embryos within the thermosensitive period (stages 20–24), and assessed several physiological and morphological hatchling traits. While embryonic size was strongly influenced by oxygen, differentiation rate did not seem to be affected. Very low oxygen concentrations and high temperatures inhibited embryo survival. In addition, oxygen availability affected incubation period and hatchling size, whereas temperature did not cause a significant variation in hatchling size. By investing energy in differentiation hypoxic embryos decreased their size.